Red kidney bean lectin is a potent cholecystokinin releasing stimulus in the rat inducing pancreatic growth. Issue 3 (1st September 1997) - Herzig, K-H; Bardocz, S; Grant, G; Nustede, R; Fölsch, U R; Pusztai, A
Abstract : Background —Lectins are proteins capable of specific binding to carbohydrates without altering their covalent structure. As an essential part of plants they are ingested in our daily diet. By binding to glycosyl side chains of receptors lectins can mimic or inhibit the action of the ligand. Oral administration of phytohaemagglutinin (PHA) in rats dose dependently induces growth of the small intestine and the pancreas by an unknown mechanism. Aims —To investigate the mechanism of PHA induced intestinal and pancreatic growth. Methods —Thirty day old male rats were pairfed for 10 days with lactalbumin as a control diet or lactalbumin plus PHA or purified soybean trypsin inhibitor (STI) as a positive control (42 mg/rat/day) with or without 20 μg of the cholecystokinin A (CCK-A) antagonist MK 329. To investigate further the effect of PHA on CCK release intestinal mucosal cells were isolated from rats which were continuously perfused in a perfusion apparatus. CCK release into the medium was assayed. Results —PHA and STI significantly stimulated growth of the pancreas and the small intestine. MK 329 blocked this growth effect in the pancreas but not in the small intestine. In vivo, PHA significantly increased CCK plasma levels from 0.75 to 6.67 (SEM 2.23) compared with 2.3 (0.35) pM in the control group. In addition, in vitro PHA dose dependently stimulated CCK release with a maximal effect at 100 ng/ml. Conclusion —In vivo and in vitro PHA is a potent stimulus for CCK release in the rat, thereby inducing pancreatic growth, whereas intestinal growth is stimulated by a CCK independent mechanism.